Immunological efficacy and tolerability of vaccination in patients with noncommunicable diseases - O. M. Drapkina; M. N. Mamedov; V. A. Kutsenko; L. N. Ryzhakova; A. V. Emelyanov; B. U. Mardanov; A. V. Kontsevaya (Российский кардиологический журнал, 2022)
Aim. To study the efficacy and tolerability of Sputnik V vaccination in patients with noncommunicable diseases (NCDs) compared with healthy individuals.Material and methods. The retrospective analysis included data from 800 men and women aged 18 to 90 who were vaccinated from February to May 2021 at the National Medical Research Center for Therapy and Preventive Medicine. Sputnik V (Gam-COVID-Vac, Russia), consisting of two doses, was used as a vaccine. The mean age of the patients was 50,46±13,16 years. Patients were questioned in two stages: before vaccination and after the first dose of vaccination. The following clinical and paraclinical investigations were carried out: saturation assessment, measurement of temperature, blood pressure and heart rate at rest, pharynx examination, auscultation of the heart and respiratory organs. The blood concentration of antibodies (IgM and IgG) was determined after 21 days and 42 days. For analysis, patients were divided into three groups. The first group included healthy individuals (n=238, 29,8%), the second group — patients with one NCD (n=385, 48,1%), and the third group — patients with two or more NCDs (n=177, 22,1%).Results. The sex composition was comparable in all three groups, while the mean age differed. In the first group, the mean age was 43,93±10,80 years, while in the second and third groups — 50,51±12,55 and 59,12±12,37 years, respectively (p<0,001). Statistical analysis was performed with adjustment for age and sex. The median blood concentration of immunoglobulin G of vaccinated individuals of the cohort after 21 days was within 4,60 [2,00; 8,40]. A comparative analysis of the groups did not reveal significant differences. After 42 days, the median concentration of immunoglobulin G increased by 4 times, which is significant (p<0,001) and amounted to 16,20 [15,80; 16,40]. In the group of healthy individuals, the concentration of immunoglobulin G was significantly higher compared to groups of individuals with one, as well as two or more NCDs. Forty-two days after vaccination, the concentration of immunoglobulin M both in the cohort and in individual groups did not change significantly compared to the level after 21 days. In addition, 47%, 38% and 40% of participants from the first, second and third groups, respectively, reported some symptoms. A temperature increase on average was detected in 13% of vaccinated individuals. The largest number of persons with fever was registered in the group of healthy individuals — 19%, in the group of patients with one NCD — 14%, and in the group with two or more diseases, the temperature increase was the lowest and amounted to 3% (p<0,001). After the first dose, 18,6% of patients reported taking additional drugs as follows: first group — 23,9%, second group — 15,1%, third group — 19,2%. These are mainly analgesic, non-steroidal anti-inflammatory and antihistamine drugs.Conclusion. Vaccination with Sputnik V increases the immunoglobulin G level in the blood after 42 days by four times compared to after 21 days. This pattern is observed both in the group of healthy individuals and in patients with one, two or more chronic NCDs. Tolerability of vaccination in all groups was comparable and did not lead to visits to healthcare facilities.